Military Effectiveness Volume 1 The First World War / [electronic resource] - Millett, Allan R.; Murray, Williamson (Cambridge : Cambridge University Press, 2010)
This three-volume study examines the questions raised by the performance of the military institutions of France, Germany, Russia, the United States, Great Britain, Japan and Italy in the period from 1914 to 1945. Leading military historians deal with the different national approaches to war and military power at the tactical, operational, strategic, and political levels. They form the basis for a fundamental re-examination of how military organizations have performed in the first half of the twentieth century. Volume 1 covers World War I. Volumes 2 and 3 address the interwar period and World War II, respectively. Now in a new edition, with a new introduction by the editors, these classic volumes will remain invaluable for military historians and social scientists in their examination of national security and military issues. They will also be essential reading for future military leaders at Staff and War Colleges.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).